World Environmental and Water Resources Congress 2009 2009
DOI: 10.1061/41036(342)112
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Indicator Bacteria Removal by Stormwater BMPs in North Carolina

Abstract: In the United

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Yet, the performance of conventional BSM is inconsistent and inadequate for removing contaminants from urban stormwater runoff that pass through the biofilters. For example, in multiple studies, conventional stormwater biofilters have been reported to leach both microbial and chemical contaminants into the stormwater as it exits the biofilters (García-Albacete et al 2014, Hathaway et al 2009, Chandrasena et al 2012, Zhang et al 2012. Such findings motivate ongoing work (Bratieres et al 2008, Li et al 2012, Hsieh and Davis 2005b, Li et al 2014, Mohanty et al 2013, Li et al 2016, Poresky et al 2016 to identify effective BSM for removing stormwater contaminants, including pathogens, pathogen indicator bacteria, and nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the performance of conventional BSM is inconsistent and inadequate for removing contaminants from urban stormwater runoff that pass through the biofilters. For example, in multiple studies, conventional stormwater biofilters have been reported to leach both microbial and chemical contaminants into the stormwater as it exits the biofilters (García-Albacete et al 2014, Hathaway et al 2009, Chandrasena et al 2012, Zhang et al 2012. Such findings motivate ongoing work (Bratieres et al 2008, Li et al 2012, Hsieh and Davis 2005b, Li et al 2014, Mohanty et al 2013, Li et al 2016, Poresky et al 2016 to identify effective BSM for removing stormwater contaminants, including pathogens, pathogen indicator bacteria, and nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…However, hybrid wetland systems are the most effective for removal of microbes which is possibly due to a longer hydraulic retention time (Wu et al, 2016). A CW system designed for treatment of residential runoff showed higher removal of Enterococci (49-61%) than E. coli (-15-45%) (Hathaway et al, 2009c). The negative removal refers to higher concentration of E. coli in the effluent than in the influent which could be due to the intrusion of microbial contaminants into CW systems by external sources.…”
Section: Removal Of Microbial Pollutantsmentioning
confidence: 99%
“…Moreover, exposure of bioretention facilities to sunlight has been shown to increase microbial removal [53]. The composition of bioretention media can play an important role in the performance of the system.…”
Section: Lid Practicesmentioning
confidence: 99%